FROM STUDYING LITERATURE TO WRITING DRAMA SCRIPTS: A CASE STUDY (Universitas Pamulang, 2017)
AbstractThe focus of the study is to encourage the students of the sixth semester of English Department, Faculty of Letters, Universitas Pamulang (UNPAM), Tangerang Selatan, Banten, Indonesia, to write the drama scripts for the drama performance to be performed. Writing script is the idea to develop the students’ ability to write and explore their interests in literature especially in drama. The data from the drama scripts were analyzed through the drama elements such as genre, plot, characters, and theme. Group of the students from each class had to produce a drama script based on the literature subject they studied in the previous semester. Most topics of the drama scripts were about old literature, new literature, and some of the aesthetic works. Yet, they could express their feeling and ideas related to the contents of the script as the young people terms in society. The result of the study showed that they were able to include the drama elements such as genre, plot, characters, and theme.Keywords: Drama Scripts, Drama Performance, Elements of Drama, Genre